Exploring perceived organisational support and resilience as antecedents of expatriates’ work and non-work spheres amid the COVID-19 pandemic - Chan, Hak Liong; Dahlia Zawawi; Toh, Pei Sung; Shian Mun Emily Gunn (Universiti Malaysia Sarawak, 2022)
Expatriates face more challenges when they are exposed to hostile environments in a foreign country. Due to the COVID-19 pandemic, most expatriates are stranded abroad without adequate support mechanisms. The aim of this paper is to empirically investigate the role of perceived organisational support (POS) and resilience in predicting expatriates’ perception of non-work constraints and work adjustment, and in turn, their withdrawal intention. Using the convenience sampling, questionnaire data was collected through social networking platforms from 205 expatriates across various industries in Malaysia. Partial least squares-structural equation modelling was employed to test the hypotheses. The results revealed that POS is influential in expatriates’ resilience, but not in their perceived non-work constraints and work adjustment. Spillover effects occur when perceived non-work constraints influence withdrawal intention. However, perceived non-work constraints are not significantly related to work adjustment. Further, work adjustment has a negative relationship with withdrawal intention. The results indicate that organisations should customise their human resource policies to improve expatriates’ resilience through webinars and counselling services during the COVID-19 crisis, which are likely to impact their work outcomes. The contribution of this study is its application of the conservation of resources theory to enrich the sparse literature on expatriation in a hostile environment.